Factor Affecting Job Satisfaction in Community Pharmacists: A Review - Sintaresmi Kusumah Wardani; Susi Ari Kristina; Nanang Munif Yasin (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Job satisfaction, especially pharmacists', must be considered, as their work is related to patient safety. This review aims to identify job satisfaction, the factors that influence it, and the instruments used to measure it in community pharmacists. This systematic review used the PRISMA methodology and was conducted in December 2022 using three search engines (PubMed, Science Direct, and Google Scholar) by retrieving articles published in the last ten years. Two researchers independently assess the quality of articles using JBI Critical Appraisal. The keywords